Benjamin and Goldman as the readers of Pascal. Benjamin’s theory of sorrow and Goldman’s theory of tragic vision - Sagnol , Marc (Sententiae, 2000)
The article describes and partially compares Walter Benjamin’s theory of sorrow and Lucien Goldman’s theory of tragic vision. The comparison is made in the light of the connections between both theories and Pascal’s philosophy. The author concludes that these theories are essentially analogous and complementary. In the author’s opinion, both theories, despite all the differences, clarify sadness and tragedy by addressing the paradox of human existence that consists in the discovery of the vast infinity of the world and the inaccessibility of transcendence, in the light of which, however, we are forced to think about our own existence. Based on the results of the review, the author emphasizes the essential parallelism and connection of both theories with Pascal’s philosophy, which to some extent can be seen as their common ground.